Le cadrage de la communication dans les médias - Marcel Burger (Communication)
This article examines the role played by linguistic units in framing communication acts within a specific media genre: broadcast debates. It discusses more specifically which concepts and methods facilitate the merging of language and communication sciences into an articulate, interdisciplinary, scientific approach.